Nieistniejąca kaplica sióstr pallotynek w Gdańsku – arcydzieło sakralnej sztuki modernistycznej - Markowska, Anna
The purpose of this article is to analyse the no longer existing chapel of the Pallotine Missionary Sisters of the Catholic Apostolate, dedicated to Our Lady of Divine Love in the context of modern art and its role in post‑war Poland. The convent chapel was erected only a year after the arrival of the sisters to Gdańsk However, its modernist structure was shaped by two subsequent renovations, carried out in 1959 and 1965. Despite its outstanding artistic and historical qualities, this original and unique creation by Sister Julitta Gołębiowska, SAC has not yet gained recognition from researchers. Drawing on the modernist concept of the Gesamtkunstwerk, Sister Julitta created a masterpiece of an immersive character. She was stimulated by vibrant discussions about modern religious art during her studies in Kraków and inspired by the realization of the Chapelle du Rosaire by the Dominican nuns in Vence (1947–1951). The ultimate design of the chapel was additionally influenced by the patriotic element of fostering Polish modernity within Gdańsk’s historical German artistic context, alongside the concepts regarding the renewal of religious life outlined in the Second Vatican Council.Sister Julitta meticulously designed the chapel, taking into account both artistic and theological considerations. The subsequent chapel constructed in the early 1990s to replace the original diverged from its predecessor’s expressive and joyful blue‑and‑‑red colour scheme. It is possible that the profound asceticism evident in this later rendition, conceived by Sister Julitta, was influenced by the political transition and the belief that it demanded distinctive qualities from Church members.
Keywords: Julitta Gołębiowska; modern art; Gdańsk; design; religious art; conven; nuns; post-war Pomerania